‘Systemic thinking’, ‘regenerative culture’, and new forms of prefigurative politics: Challenges for the global left - Esteves, A. M. (Globalizations, 2020)
One of the aspects of the current crisis of the Left is an ‘epistemological blindness’ that prevents it from identifying opportunities for its own renewal. That includes the dismissal of the contribution of prefigurative forms of collective action which do not fit its institutionalized orthodoxies. Their most significant expression is a range of grassroots initiatives based on ‘systemic thinking’ and aimed at promoting a ‘regenerative culture’. It includes non- capitalist economic initiatives, such as those of the transition movement, social and solidarity economy and the Global Ecovillage Network, as well as of the temporary communities created by Occupy Wall Street movement and the Dakota Access Pipeline protests. They regard social polarization, patriarchy, and the crisis of democracy as interconnected dimensions of a civilizational dysfunction that asks for whole-systems solutions. Such approach, if adopted by the Left, may contribute to its renewal and political strengthening.